In vitro digestive properties and the bioactive effect of walnut green husk on human gut microbiota - Zhao, Xiaolan; Ying, Jiabao; Wang, Zhuochen; Wang, Yulu; Li, Zhen; Gu, Tianyi; Liu, Shujun; Li, Yulong; Liu, Bing; Xin, Fengjiao; Wen, Boting (Frontiers in Microbiology, 2024)
Walnut green husk (WGH) is a waste byproduct from walnut industry. However, it is not wellknown about its bioactive effect on human gut health. This study conducted in vitro digestion and fermentation experiments to study the bioactive effect of WGH. Microbial fermentation was the primary mechanism to efficiently release phenolics and flavonoids, resulting in more excellent antioxidant capacities (ABTS, DPPH, and FRAP assays), which reached a highest value with 14.82 ± 0.01 mg VcE/g DW, 3.47 ± 0.01 mmol TE/g DW and 0.96 ± 0.07 mmol FeSO4• 7H2O/g DW respectively. The surface microstructure of WGH became loose and fragmented after microbial fermentation. The analytical results of gut microbiota demonstrated that WGH could significantly increase the relative abundance of Proteobacteria in phylum level and Phascolarctobacterium in genus level while certain pro-inflammatory bacteria (such as Clostridium_sensu_stricto_1, Dorea, Alistipes and Bilophila) was inhibited. Additionally, 1373 differential metabolites were identified and enriched in 283 KEGG pathways. Of which some metabolites were significantly up-regulated including ferulic acid, chlorogenic acid, umbelliferone, scopolin, muricholic acid and so forth. These results indicated that WGH could have antioxidant and anti-inflammatory activities in the human gut, which could improve the economical value of WGH in the food industry.